Når militæret skriver krigshistorier: En analyse af David Abrams’ Fobbit - Toft, Christine Strandmose (Passage - Tidsskrift for litteratur og kritik, 2018)
Christine Strandmose Toft: “When the Military Writes War Stories. A Reading of David Abrams’ Fobbit” This article examines David Abram’s novel Fobbit (2012), a satirical comedy about Chance Gooding who works as a public affairs officer in the Army. First part of the article concerns the representation of the military’s attempt to represent war and asks why it is of paramount importance to the military to control the public’s view of the Iraq War. The second part considers the novel as meta-representation and discusses the kind of laughter it produces and its critical potential.